Effect of Pilates Mat Exercises on Neuromuscular Efficiency of the Multifidus and Internal Oblique Muscles in a Healthy Ballerina - Panhan, Ana C.; Goncalves, Mauro [UNESP]; Eltz, Giovana D. [UNESP]; Villalba, Marina M. [UNESP]; Cardozo, Adalgiso C. [UNESP]; Berzin, Fausto (J Michael Ryan Publishing Inc, 2019)
Physical training has frequently been indicated for ballet dancers to strengthen their trunk muscles, improve their performance, and avoid injuries. The current authors hypothesized that these dancers could benefit from Pilates exercises to stabilize their trunk muscles and improve joint stability and neuromuscular efficiency (NME). Our study aimed at evaluating the NME and isometric strength of the internal oblique (IO) and multifidus (MU) muscles in a healthy 24-year-old classical ballerina before and after an 8-week Pilates exercise intervention. The muscles were tested with electromyography (EMG) and a dynamometer, and the resulting torque and EMG values were used to calculate the NME. Based on the results, the Pilates exercises could improve the NME of the muscles tested, since the torque increased and the EMG activity decreased after the intervention.